2021
DOI: 10.1101/2021.03.17.21253782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

B.1.1.7 became the dominant variant in Lebanon

Abstract: Recently, a new variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) designated VOC 202012/01 (or B.1.1.7 lineage) has become highly prevalent in several countries, after first being described in the United Kingdom (UK). Its rate of transmission has been estimated to be increased compared to other lineages. In the present study, we show the emergence, dominance and the rapid spread of the B.1.1.7 lineage in Lebanon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Genome sequencing is the gold method to confirm the new variant, but observational studies provide also stronger evidence if similar models are observed in multiple countries, especially when randomized studies are not possible. In Lebanon, surveillance data from Beirut Medical Center and Bahman Hospital showed a rapid and dramatic increase in S-negative profile in PCR testing for SARS-CoV-2 in the first twelve days in January, reaching approximately 60% of positive cases and 95% in February [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing is the gold method to confirm the new variant, but observational studies provide also stronger evidence if similar models are observed in multiple countries, especially when randomized studies are not possible. In Lebanon, surveillance data from Beirut Medical Center and Bahman Hospital showed a rapid and dramatic increase in S-negative profile in PCR testing for SARS-CoV-2 in the first twelve days in January, reaching approximately 60% of positive cases and 95% in February [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the estimated sensitivity of the STANDARD M10 was higher for the E gene than for the ORF1ab gene; indeed, the latter was not detected in 4.5% of positive samples. A significant proportion of the ORF1ab dropout has been reported for both Alpha [24] and Delta [25] VOCs. Notably, among Alpha VOCs detected in Lebanon, the ORF1ab dropout was observed in all samples with S gene dropout [24].…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of the ORF1ab dropout has been reported for both Alpha [24] and Delta [25] VOCs. Notably, among Alpha VOCs detected in Lebanon, the ORF1ab dropout was observed in all samples with S gene dropout [24]. Similarly, in our study, 6 of 9 samples negative for the ORF1ab gene had RdRp gene dropout in the Allplex 2019-nCoV assay.…”
Section: Discussionmentioning
confidence: 99%
“…This variant was observed to spread in several countries including the Romania [40], East Germany [33], Lebanon [41], Czech Republic and Slovakia [42].…”
Section: Covid-19 Variantsmentioning
confidence: 99%